Ovarian carcinoma histotype determination is highly reproducible, and is improved through the use of immunohistochemistry. Issue 7 (7th March 2014) - Köbel, Martin; Bak, Julia; Bertelsen, Björn I; Carpen, Olli; Grove, Anni; Hansen, Estrid S; Levin Jakobsen, Anne‐Marie; Lidang, Marianne; Måsbäck, Anna; Tolf, Anna; Gilks, C Blake; Carlson, Joseph W
<x xml:space="preserve">Abstract</x> Aims To assess the variation in ovarian carcinoma type diagnosis among gynaecological pathologists from Nordic countries, and whether a rationally designed panel of immunohistochemical markers could improve diagnostic reproducibility. Methods and results Eight pathologists from four countries (Sweden, Denmark, Norway, and Finland) received an educational lecture on the diagnosis of ovarian carcinoma type. All tumour‐containing slides from 54 ovarian carcinoma cases were independently reviewed by the participants, who: (i) determined type purely on the basis of histology; (ii) indicated whether they would apply immunohistochemistry in their routine practice; and (iii) determined type after reviewing the staining results. The results for six markers (WT1, p53, p16, HNF‐1β, ARID1A, and progesterone receptor) were determined for all 54 cases, by staining of a tissue microarray. The median concordance with central review diagnosis was 86%, and significantly improved to 90% with the incorporation of immunostaining results (P = 0.0002). The median interobserver agreement was 78%, and significantly improved to 85% with the incorporation of immunostaining results (P = 0.0002). Conclusions Use of the immunostaining results significantly improved both diagnostic accuracy and interobserver agreement. These results indicate that ovarian carcinoma type can be reliably diagnosed by pathologists from different countries, and also demonstrate that immunohistochemistry has an important role in improving diagnostic accuracy and agreement between pathologists.